Hubungan Karateristik Pasien Daibetes Melitus Tipe 2 Dengan Perilaku Pencegahan Penularan Covid-19 Di Pelayanan Rawat Jalan Rumah Sakit Panti Rahayu Yogyakarta - Puji Lestari, Monica; Subiyanto, Paulus; Ratnawati, Emilia (STIKes Panti Rapih, 2023)
ABTRACT Background: Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by a new type of Coronavirus. The disease began with the emergence case of pneumonia in Wuhan, China at the end of December 2019. The symptoms that include COVID-19 infection are acute respiratory distress such as fever, cough, and asthma. The prevalence of diabetes for COVID-19 patients is almost three times higher with poor conditions (16.2%) compare to those who were not in bad (5.7%). Goal: This research aims to find out the characteristic relation of Diabetes Mellitus Type 2 patients with the prevention infection of COVID-19 behavior in Panti Rahayu Hospital Yogyakarta. Method: This study used descriptive cross-sectional type conducted of Diabetes Mellitus Type 2 patients with a sample of 33. There were 39 participants of this research with Diabetes Mellitus type2 cases in Panti Rahayu Hospital. The researcher found there were 33 respondents with accidental sampling techniques. The research instrument used was a questionnaire. Result: The results of the data were age > 60 years old (48,5%), female (66,7%), elementary school, junior high school, and senior high school (81,8%), not working (51,5%), and COVID-19 good prevention behavior (81.8%) which includes good 3M (81.8%), less body immunity increase (63.6%), good indoor environmental sanitation (72.7%). The statistical tests that used are chi-square and fisher test alternative test obtained age-behavior results (p value 0.232), gender-behavior (p value 1,000), education-behavior (p value 1,000) and occupation-behavior (p value 0.398). Conclusion: The researcher concluded there was a relation between the characteristic of Diabetes Mellitus type 2 patients and the prevention infection of COVID-19 behavior in Panti Rahayu Hospital Yogyakarta. Keyword: Diabetes Mellitus Type 2, Prevention Infection Behavior, COVID-19